Faktor-faktor Risiko Penyebaran Escherichia coli O157:H7 pada Sapi Bali di Kuta Selatan, Badung, Bali (RISK FACTORS FOR DISSEMINATION OF ESCHERICHIA COLI O157:H7 IN BALIN CATTLE IN SOUTH KUTA, BADUNG, BALI) - Rinca, Korbinianus Feribertus; Nindhia, Tjokorda Sari; Suardana, I Wayan (Jurnal Veteriner, 2016)
Escherichia coli O157:H7 is a strain of E.coli which has ability to produce toxin known as shiga-liketoxin. Shiga like toxin can cause colitis haemorrhagic and hemolytic uremic syndrome in human. However,in calves, it can cause diarrhea, while in adult cattle can be career. Cattle are primary reservoir of E. coliO157:H7. Study of dissemination pattern of E.coli O157:H7 was carried out using 60 samples of cattlefeces. This is a cross sectional study and samples were collected using purposive sampling technique.Based on statistic calculation using chi-square and Odds ratio tests, it was found some risk factorsaffected the dissemination of E.coli O157:H7 infection in South Kuta District, Badung, Bali. Some of thosewere the altitude of sea level that showed the cattle which were maintained in highland showed more riskthan cattle that was in the lowland, with odds ratio value 1.12. The management animal husbandryshowed cattle that maintained in captive management were in higher risk than cattle that was notmanaged in captive system, with odds ratio value 2.50. The type of captive floor, which made from cementwas higher risk than cattle that was raised in captive floor which were made from non cement with oddsratio value 6.22. The chi-square test result did not show a significant difference to the dissemination of E.coli O157:H7 in the South Kuta-district.
Keywords: risk factor; dissemination E.coli O157:H7; cattle; South Kuta